PENINGKATAN RASIO C/N LIMBAH CAIR TAHU DENGAN PENCAMPURAN SEKAM PADI UNTUK MENDAPATKAN POTENSI BIOGAS DAN ENERGI LISTRIK - Aditya, Muhammad Suryo; Jelita, Marhama (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
Tofu liquid waste has a C/N ratio of 4.68 which is below the standard for biogas formation, namely 20-30. Increasing the C/N ratio of tofu liquid waste was carried out by adding raw materials that had a high C/N ratio, namely rice husks of 145.35. The amount of raw material mixed with tofu liquid waste and rice husks is determined by varying the C/N ratio according to standards with variations of 20, 22, 24, 26, 28, and 30 to get the best potential for biogas and electrical energy using the Anaerobic Fermentation method and software assistance. Superpro. The amount of rice husk raw material with a C/N ratio of 20, 22, 24, 26, 28, and 30 respectively 97.77 kg, 112.33 kg, 127.37 kg, 142.90 kg, 158.98 kg, and 175.60 kg. The best potential for biogas and electrical energy is at a C/N ratio of 30 with a raw material amount of 800 liters of tofu liquid waste and 175.60 kg of rice husk waste, amounting to 327.56 m3 and 1,539.53 kWh. It can be concluded that the raw material of rice husks can increase the C/N ratio of tofu liquid waste which is still below the standard for biogas formation, so that mixing tofu liquid waste with rice husks can increase the potential for biogas and electrical energy. Keywords: C/N Ratio, Tofu Liquid Waste, Rrice Husk, Biogas